2021
DOI: 10.1111/are.15477
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cost of acute and chronic exposure of Nile tilapia (Oreochromis niloticus) to different levels of salinity

Abstract: Tilapias are a prominent aquaculture fish species, placing second only to carps in terms of the world's fish production (FAO, 2018).According to FAO (2018), their production is predicted to increase from 58% in 2016 to about 62% in 2030, and is expected to surpass that of carp by the year 2025 (Ahmadi et al., 2016). This is because of their resilience to varied stress conditions and their characteristic fast growth rate, which make them a preferred aquaculture species in most places of the world, including Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Nevertheless, it has been suggested that Nile tilapia is also suitable for brackish water aquaculture for the salinity level up to 15 ppt ( 3 , 8 ). The lower and upper lethal temperatures for Nile tilapia are 11–12°C and 42°C, respectively ( 2 , 3 ), whereas the upper lethal salinity varies from about 20 ppt to about 40 ppt depending on the water temperature and the rate of salinity change (i.e., direct transfer vs. gradual acclimatization) ( 2 , 9 11 ). The comparatively high performance in adaptability to a broad range of environmental conditions render Nile tilapia farming prosperous across different geographical locations, ranging from tropical to temperate climates, and from freshwater to brackish water.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that Nile tilapia is also suitable for brackish water aquaculture for the salinity level up to 15 ppt ( 3 , 8 ). The lower and upper lethal temperatures for Nile tilapia are 11–12°C and 42°C, respectively ( 2 , 3 ), whereas the upper lethal salinity varies from about 20 ppt to about 40 ppt depending on the water temperature and the rate of salinity change (i.e., direct transfer vs. gradual acclimatization) ( 2 , 9 11 ). The comparatively high performance in adaptability to a broad range of environmental conditions render Nile tilapia farming prosperous across different geographical locations, ranging from tropical to temperate climates, and from freshwater to brackish water.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate handling conditions are essential to achieve an acceptable product in terms of the welfare of the fish and the meat quality (Gatica et al, 2008;Mendes et al, 2017). Studies have described reduced stress in fish after handling under isosmotic conditions, as it reduces the need for physiological energy for osmoregulation and the maintenance of homeostasis (Wurts, 1995;Kombat et al, 2021). The use of salt during management routines is a common practice in fish farms, however, few studies have evaluated animals during depuration in a saline environment.…”
Section: Introductionmentioning
confidence: 99%